Moral Character Development through the Integration of Classroom Instruction and Madrasah Culture: A Qualitative Case Study at MI ELPIST Temanggung, Indonesia - Kurniyah Kurniyah; Raharjo Raharjo (AL-ISHLAH: Jurnal Pendidikan, 2026)
Moral character education has become increasingly important in Islamic elementary schools amid rapid social and technological change. Although previous studies have examined character education in madrasahs, limited attention has been given to how classroom instruction and madrasah culture operate as an integrated mechanism in private non-pesantren Islamic elementary schools. This study investigates how students' moral character is developed through the integration of learning and madrasah culture at MI ELPIST Temanggung. This study employed a qualitative intrinsic case study conducted over four months. Purposive sampling involved one principal, five teachers, five students, and five parents. Data were collected through observations, semi-structured interviews, and document analysis, and analyzed using the Miles and Huberman interactive model with thematic coding, triangulation, member checking, and an audit trail to ensure trustworthiness. The findings reveal that students' moral character is fostered through the integration of value-oriented classroom instruction, teacher role modelling, religious habituation, supportive madrasah culture, and sustained school–parent collaboration. These interconnected practices create continuous opportunities for students to internalize moral values through both formal learning and everyday educational experiences. The study proposes an integrated instruction–culture mechanism demonstrating that moral character development is strengthened when curriculum implementation, teacher practices, institutional culture, religious routines, and family support operate as a coherent educational ecosystem. This model extends existing literature by explaining how these dimensions interact to facilitate moral internalization in a private non-pesantren Islamic elementary school and provides practical guidance for strengthening character education in similar contexts.